2011
DOI: 10.1038/nrclinonc.2011.177
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of HER2-positive breast cancer: current status and future perspectives

Abstract: The advent of HER2-directed therapies has significantly improved the outlook for patients with HER2-positive early stage breast cancer. However, a significant proportion of these patients still relapse and die of breast cancer. Trials to define, refine and optimize the use of the two approved HER2-targeted agents (trastuzumab and lapatinib) in patients with HER2-positive early stage breast cancer are ongoing. In addition, promising new approaches are being developed including monoclonal antibodies and small-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
635
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 775 publications
(658 citation statements)
references
References 158 publications
5
635
1
7
Order By: Relevance
“…It dimerizes with the other members of the ERB family to form heterodimers and initiate signal transduction (Khasraw and Bell 2012). It has been reported to be overexpressed in 20% of breast and 22% of gastric cancers, although different studies have reported varying results (Bang et al, 2010;Arteaga et al, 2011). In a study investigating 200 patients, HER2 overexpression was reported in 23% of patients, while another study that analyzed 248 patients showed overexpression of HER2 mRNA and/or proteins and amplification of genes in 22.6% of patients (Yano et al, 2006;.…”
Section: Discussionmentioning
confidence: 99%
“…It dimerizes with the other members of the ERB family to form heterodimers and initiate signal transduction (Khasraw and Bell 2012). It has been reported to be overexpressed in 20% of breast and 22% of gastric cancers, although different studies have reported varying results (Bang et al, 2010;Arteaga et al, 2011). In a study investigating 200 patients, HER2 overexpression was reported in 23% of patients, while another study that analyzed 248 patients showed overexpression of HER2 mRNA and/or proteins and amplification of genes in 22.6% of patients (Yano et al, 2006;.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Her-2 overexpression leads to an aggressive form of breast cancer, 10 which comprises 25% of all breast cancer cases. 11 The Her-2 positive breast cancer patients have a lower survival rate than patients without Her-2 overexpression. Her-2 has been used as a predictive and prognostic biomarker of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to identify biomarkers and mechanisms of resistance to select subpopulations of patients who are likely responders and to develop new regimens or agents that target resistance pathways to reverse resistance. Various mechanisms of resistance have been proposed for both de novo and acquired trastuzumab resistance, e.g., activation of other RTKs (e.g., ErbB3 or IGF-1R), steric hindrance of ErbB2-trastuzumab interaction by glycoproteins (e.g., MUC4), inhibition of trastuzumab binding to ErbB2 by cleavage of ErbB2 extracellular domain (p95ErbB2) and activation of PI3K pathway or SRC [7,8]. We previously demonstrated that loss of the phosphatase and tensin homolog (PTEN), a negative regulator of the PI3K/AKT pathway, confers de novo trastuzumab resistance in ErbB2-overexpressing breast cancer [9].…”
Section: Introductionmentioning
confidence: 99%